Contagion and Interdependencies: A Dynamic Connectedness approach among Implied Volatilities - Gilbert Kwabena Amoako; Ebenezer Boateng; Emmanuel Asafo-Adjei; Daniel Kofi Amoanyi; Anokye M. Adam (Cogent Economics & Finance, 2022)
This study employs the TVP-VAR approach to capture the degree of interdependencies and contagion among sixteen implied volatilities. The 16 daily implied volatility indices comprise the implied volatility from various financial assets, such as conventional equities, commodities, and currencies, in national, regional, or worldwide indexes. After missing data were expunged, the daily data span between 5 August 2016 and 18 August 2021 inclusive, yielding 1758 observations. We reveal strong evidence to support that the network of implied volatilities is highly connected. Nonetheless, dynamic connectedness varies across time demonstrating that the markets are heterogenous and adaptive. The rise in connectedness during crisis and non-crisis periods indicates that both contagion and interdependencies are germane to implied volatilities. The outcome from the net directional connectedness underscores that the CBOE Euro Currency Volatility, CBOE Crude Oil Volatility, CBOE Gold Volatility, Hang Seng Index (HSI) and CAC 40 VIX are net persistent receivers whereas CBOE Russell 2000 Volatility, CBOE NASDAQ 100 Volatility, DJIA Volatility, CBOE VIX and CBOE OEX Implied Volatility are persistent net transmitters. The size and direction of net connectedness enlighten investors to pair persistent net receivers and transmitters. Practical, policy and theoretical implications are provided.
Keywords: 330; adaptability; economic events; heterogeneity; net persistent receivers; time-varying